Improvement of the safety of a clinical process using failure mode and effects analysis: Prevention of venous thromboembolic disease in critical patients - Viejo Moreno, R; Sánchez-Izquierdo Riera, J Á; Molano Álvarez, E; Barea Mendoza, J A; Temprano Vázquez, S; Díaz Castellano, L; Montejo González, J C (Medicina intensiva, 2016)
To improve critical patient safety in the prevention of venous thromboembolic disease, using failure mode and effects analysis as safety tool. A contemporaneous cohort study covering the period January 2014-March 2015 was made in 4 phases: phase 1) prior to failure mode and effects analysis; phase 2) conduction of mode analysis and implementation of the detected improvements; phase 3) evaluation of outcomes, and phase 4) (post-checklist introduction impact. Patients admitted to the adult polyvalent ICU of a third-level hospital center. A total of 196 patients, older than 18 years, without thromboembolic disease upon admission to the ICU and with no prior anticoagulant treatment. A series of interventions were implemented following mode analysis: training, and introduction of a protocol and checklist to increase preventive measures in relation to thromboembolic disease. Indication and prescription of venous thrombosis prevention measures before and after introduction of the measures derived from the failure mode and effects analysis. A total of 59, 97 and 40 patients were included in phase 1, 3 and 4, respectively, with an analysis of the percentage of subjects who received thromboprophylaxis. The failure mode and effects analysis was used to detect potential errors associated to a lack of training and protocols referred to thromboembolic disease. An awareness-enhancing campaign was developed, with staff training and the adoption of a protocol for the prevention of venous thromboembolic disease. The prescription of preventive measures increased in the phase 3 group (91.7 vs. 71.2%, P=.001). In the post-checklist group, prophylaxis was prescribed in 97.5% of the patients, with an increase in the indication of dual prophylactic measures (4.7, 6.7 and 41%; P<.05). There were no differences in complications rate associated to the increase in prophylactic measures. The failure mode and effects analysis allowed us to identify improvements in the prevention of thromboembolic disease in critical patients. We therefore consider that it may be a useful tool for improving patient safety in different processes.